Menyoroti Maraknya Penipuan Investasi Bodong di Era Digital dalam Bentuk Pinjaman Online Ilegal dengan Modus Pinjaman Cepat dan Bunga yang Rendah di Indonesia - Tito Afrianto (CV Rewang Rencang, 2025)
The rise of illegal online lending in Indonesia has created significant problems related to financial fraud that harm society, particularly through promises of quick loans and low interest rates. The modus operandi used by illegal lenders often involves manipulative tactics, such as drastically increasing interest rates after the loan is disbursed and imposing hidden fees that burden borrowers. In addition, threats of personal data exposure and intimidation during debt collection are key strategies used to pressure victims. Although regulations exist to govern the online lending sector, their implementation remains weak in addressing these illegal practices. This study aims to analyze the social and economic impacts of the proliferation of illegal online lending and evaluate the effectiveness of law enforcement in Indonesia. The method used is a normative legal approach with legislative and comparative analysis, involving a review of national and international regulations as well as the application of sanctions against offenders. The results show that despite efforts to address the issue, gaps in regulation and supervision still allow illegal lending practices to persist. Therefore, regulatory improvements and stronger oversight are needed to protect consumers from the negative impacts of illegal online lending.